DETERMINANTS OF GEN Z PURCHASE INTENTION: THE INTERVENING ROLE OF PERCEIVED VALUE - Al Zahwa, Naviza Yulia; Handoko, Yunus; Maskan, Mohammad (Distribusi - Journal of Management and Business, 2026)
The development of technology has changed consumer behavior, especially among Generation Z, who are known as natives and are active in interacting on e-commerce platforms and social media. The phenomena of live shopping, influencer credibility, and user-generated content (UGC) have become key strategies capable of shaping consumers' purchase intentions. This study aims to analyze the influence of live shopping, influencer credibility, and user-generated content on purchase intention, with perceived value as a mediating variable among Generation Z in Surabaya. This research uses a quantitative approach with a survey method. The research population consists of Generation Z aged 12–27 years in Surabaya who actively shop online. The sampling technique uses purposive sampling. Data were collected through questionnaires and analyzed using path analysis with the assistance of SmartPLS 3.0 statistical software. The results show that live shopping and user-generated content have a positive and significant effect on Generation Z's purchase intention. Influencer credibility does not have a direct effect on purchase intention. Influencer credibility and user-generated content have a positive effect on perceived value. Perceived value does not affect purchase intention and does not function as a mediating variable. These findings indicate that Generation Z's purchase intention is more influenced by direct factors and shopping experience than by perceived value. The practical implications of this study emphasize the importance of marketing strategies based on interactive content, shopping experience, and ease of transaction. Future research is recommended to integrate additional variables and expand the context and research objects to increase the generalizability of the research.